2002
DOI: 10.1152/ajpregu.00346.2001
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase and oxidative stress in Dahl salt-sensitive and -resistant rats

Abstract: The roles of oxidative stress and renal superoxide dismutase (SOD) levels and their association with renal damage were studied in Dahl salt-sensitive (S) and salt-resistant (R)/Rapp strain rats during changes in Na intake. After 3 wk of a high (8%)-Na diet in S rats, renal medullary Cu/Zn SOD was 56% lower and Mn SOD was 81% lower than in R high Na-fed rats. After 1, 2, and 3 wk of high Na, urinary excretion of F(2)-isoprostanes, an index of oxidative stress, was significantly greater in S rats compared with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
137
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 31 publications
15
137
0
Order By: Relevance
“…Salt loading increases the excretion of isoprostanes in the hypertensive Dahl salt-sensitive rat (7). It is interesting that in Figure 1.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Salt loading increases the excretion of isoprostanes in the hypertensive Dahl salt-sensitive rat (7). It is interesting that in Figure 1.…”
Section: Discussionmentioning
confidence: 91%
“…ROS activate mitogen-activated protein kinase in renal tubule cells (38), contribute to hypertrophic responses to Ang II (38) and to cellular injury (39), and increase fibrogenic matrix protein synthesis in mesangial cells (40). A high salt intake enhances oxidative stress in rat skeletal muscle arterioles and vessels (23) and increases BP, protein excretion, and renal fibrosis and worsens renal function in several models of chronic renal failure (7,38,(41)(42)(43) and accelerates the decline of renal function in patients with chronic renal failure (44). Conversely, salt restriction ameliorates renal disease progression in animal models (42) and is recommended for patients with chronic renal failure (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Increased activity of the NAD(P)H oxidase system is expected to be associated with reduced NO levels, vascular dysfunction, hypertension and salt sensitivity. [4][5][6] The latter, is known to be associated with reduced NO bioactivity [7][8][9][10][11][12][13] and increased superoxide production. 5,6 Consequently, genetic and/or disease-induced changes in NADPH oxidase activity and superoxide formation may play an important role in the pathogenesis of saltsensitive hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Several enzymes have been implicated as possible sources of elevated ROS in hypertension, including NADPH oxidase, 14,15 xanthine oxidase, 16 NO synthase (NOS), 17 cyclooxygenase, 18 and mitochondrial electron transport leakage. 19 It has been suggested that reductions of enzymes that scavenge ROS, such as superoxide dismutases (SOD), 20 catalase, and glutathione peroxidase (GPx), may also play a role. In the present study, we explored which of these many pathways most importantly determines the susceptibility of the SS rat to salt-induced hypertension.…”
mentioning
confidence: 99%